PENGARUH KEPEMIMPINAN TRANSFORMASIONAL DAN INOVASI TERHADAP PENINGKATAN KEPUASAN KERJA PEGAWAI DI KANTOR KECAMATAN BOGOR SELATAN - Prescillia, Angela; Iskandar, Abubakar; Subagdja, R. Oetje (Administratie: Jurnal Administrasi Publik, 2021)
South Bogor District is an agency structurally under the Bogor City Government. In achieving the satisfaction obtained by employees, transformational leadership and innovation are needed to foster employee morale. The purpose of this study is to explain transformational leadership affects employee job satisfaction and describe new innovations affect job satisfaction. The research design is Cross Sectional. This research was conducted in South Bogor District, Bogor City. The population in this study were all existing employees, while the research sample was 33 people. Data was collected using a questionnaire. Data were analyzed using descriptive statistics. The research shows that the stimulus given by the leader with a correlation coefficient of 0.696 means that the relationship between the stimulus given by the leader and the results achieved is very close. Likewise, the corrections made by the leadership with a correlation coefficient of 1,000 means that the relationship between the corrections made by the leadership and the results of the work carried out by employees is very close. The correlation coefficient of informatics technology is 0.354, which means that the relationship between information technology used by employees and the work standards that have been determined is quite close.